Social networks applied to distance education courses - analysis of interaction in discussion forums - Gottardo, Ernani; Noronha, Robinson Vida (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
Driven by public policies, distance education courses or EAD are now a reality in the Brazilian educational system. However, a major difficulty faced by professionals and institutions involved in this type of education refers to the effective monitoring of students. One alternative used by the scientific community to deal with this problem have been investigating techniques for exploring the data stored by the technological systems used, trying to turn them into useful information. This work demonstrated some possibilities of using social network analysis techniques in order to obtain information from the interaction in discussion forums. In the experiments some potentially useful information was obtained, indicating the feasibility of this proposal.